Profitabilitas dan Audit Delay: Studi Kasus pada Perusahaan Properti dan Real Estat Indonesia - Tiana Fenny Krisdina; Yuri Fauziyyah; Rima Ismayanti (Universitas Muhammadiyah Palembang, 2025)
Purpose– This study aims to investigate how profitability affects audit delay. The research was conducted on property and real estate companies Indonesia Stock Exchange (IDX) from 2019 to 2023. Design/methodology– The type of research used is associative research. The data used in this study is secondary data obtained from the IDX official website (www.idx.co.id). Methods of data collection using the method of documentation. The data analysis used is quantitative analysis. The analysis technique is simple linear regression analysis with the help of the using IBM SPSS Statistics 25 application. Findings - The results of the study that the variable of profitability, have a significant positive effect on the audit delay of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX).